2021
DOI: 10.1038/s43587-021-00073-z
|View full text |Cite|
|
Sign up to set email alerts
|

APOE4 accelerates advanced-stage vascular and neurodegenerative disorder in old Alzheimer’s mice via cyclophilin A independently of amyloid-β

Abstract: he APOE4 variant of apolipoprotein E is the strongest genetic risk factor for AD 1 . One and two APOE4 alleles increase risk for AD by approximately 4-and 15-fold, respectively, compared to the more-common APOE3 gene that carries lower risk for AD 1 . Besides accelerating onset and progression of dementia, APOE4 is associated with different brain pathologies. For example, APOE4 accelerates BBB breakdown and degeneration of brain capillary pericytes 2,3 that maintain BBB integrity [4][5][6] and leads to cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 65 publications
(176 reference statements)
5
88
0
Order By: Relevance
“…So far, very few studies have visualized the BBB integrity by using MRI in animal models of AD. Montagne et al recently showed an impaired BBB integrity by using DCE-MRI assisted with Gd-DTPA in 5×FAD and APOE4 mice [202] (Figure 2a-d) (Table 3). Dickie et al reported that DCE-MRI did not detected the difference between the TgF344 and wild-type rats at 18 months-of-age, and that increased BBB water permeability was detected by using multi-flip angle multi-echo (MFAME) water-exchange MRI in TgF344 rats compared to wild-type [203].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…So far, very few studies have visualized the BBB integrity by using MRI in animal models of AD. Montagne et al recently showed an impaired BBB integrity by using DCE-MRI assisted with Gd-DTPA in 5×FAD and APOE4 mice [202] (Figure 2a-d) (Table 3). Dickie et al reported that DCE-MRI did not detected the difference between the TgF344 and wild-type rats at 18 months-of-age, and that increased BBB water permeability was detected by using multi-flip angle multi-echo (MFAME) water-exchange MRI in TgF344 rats compared to wild-type [203].…”
Section: Discussionmentioning
confidence: 93%
“…[81] T2* Tg SwDI mice [145] T2*w APP23 mice [144] DCE 5×FAD, APOE mice [202] MFAME-DCE TgF344 rats [203,204] T2*w,…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…Dynamic contrast-enhanced (DCE)-MRI has been used to detect the impaired BBB integrity in the hippocampus of patients with early AD [ 244 ]. Montagne et al recently demonstrated impaired BBB integrity in 5 × FAD and APOE4 mice compared to wild-type mice by using DCE-MRI assisted with Gd-DTPA [ 141 ] ( Figure 2 a–d) ( Table 3 ). Dickie et al reported that DCE-MRI failed to detect the difference between the TgF344 rats and wild-type rats at 18 months-of-age and that the increased BBB water permeability was detected by using multi-flip angle multi-echo (MFAME) water-exchange MRI in TgF344 rats compared to wild-type rats [ 245 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blue, lectin+ endothelial profiles; scale bar, 20 μm. Reproduced with permission from [ 141 ] from Springer Nature. ( e – h ) High-resolution magnetic resonance angiography (MRA).…”
Section: Figurementioning
confidence: 99%
“…This CBF reduction has been associated with cognitive changes in mice, including a loss of ability to sustain attention (Marshall et al, 2001). Both ApoE4 transgenic and APP/PS1 mice revealed CBF reduction prior to neuronal and synaptic dysfunctions (Guo et al, 2019;Montagne et al, 2021).…”
Section: Cerebral Blood Flow Alterations In Alzheimer's Diseasementioning
confidence: 99%